The Effect of Information Security, User Perceived Convenience and Brand Image on the Decision to Use the Neo Bank M-Banking Application Through Trust as an Intervening Variable - Lutfi, Ridwan; Shiratina, Aldina (Dinasti Publisher, 2025)
This study aims to determine the Influence of Information Security, Perceived Ease of Use of the Mobile Banking Application by Users and Brand Image on the Decision to Use the Neo Bank Mobile Banking Application through Trust as an Intervening Variable. The research method used is a quantitative causal survey method, where the variables used in this study include 3 (three) independent variables, namely perceived ease of use, information security and brand image, while the dependent variable is the Decision to Use with a total of 183 respondents. Data analysis used in this study is the Partial Least Square (PLS) method using SmartPLS 3. The results of the study indicate that information security, ease of use, brand image, and trust have a significant positive effect on the decision to use the application. Information security and ease of use not only increase the decision to use directly, but also through increasing user trust. Similarly, a positive brand image is able to build trust, which in turn encourages the decision to use. Trust is proven to be an important factor that mediates the influence of these variables, so that the higher the level of security, ease, and brand image, the greater the tendency of users to use the application actively and continuously